KnowledgeBoat Logo

Mathematics

From the figure (1) given below, find the values of :

(i) 2 sin y - cos y

(ii) 2 sin x - cos x

(iii) 1 - sin x + cos y

(iv) 2 cos x - 3 sin y + 4 tan x

From the figure, find the values of (i) 2 sin y - cos y (ii) 2 sin x - cos x (iii) 1 - sin x + cos y (iv) 2 cos x - 3 sin y + 4 tan x. Trigonometrical Ratios, ML Aggarwal Understanding Mathematics Solutions ICSE Class 9.

Trigonometrical Ratios

54 Likes

Answer

In right-angled ∆BCD,

Using pythagoras theorem we get,

⇒ BC2 = BD2 + CD2

⇒ BC2 = 92 + 122

⇒ BC2 = 81 + 144

⇒ BC2 = 225

⇒ BC = 225\sqrt{225}

⇒ BC = 15.

In a right-angled ∆ABC,

Using pythagoras theorem

⇒ AC2 = AB2 + BC2

⇒ AB2 = AC2 - BC2

⇒ AB2 = 252 - 152

⇒ AB2 = 625 - 225 = 400

⇒ AB = 400\sqrt{400}

⇒ AB = 20

(i) We know that

In right-angled ∆BCD,

sin y = PerpendicularHypotenuse\dfrac{\text{Perpendicular}}{\text{Hypotenuse}}

= BDBC=915=35.\dfrac{BD}{BC} = \dfrac{9}{15} = \dfrac{3}{5}.

cos y = BaseHypotenuse\dfrac{\text{Base}}{\text{Hypotenuse}}

= CDBC=1215=45.\dfrac{CD}{BC} = \dfrac{12}{15} = \dfrac{4}{5}.

Substituting values in 2 sin y - cos y we get :

2 sin y - cos y=2×3545=6545=25.\Rightarrow \text{2 sin y - cos y} = 2 \times \dfrac{3}{5} - \dfrac{4}{5} \\[1em] = \dfrac{6}{5} - \dfrac{4}{5} \\[1em] = \dfrac{2}{5}.

Hence, 2 sin y - cos y = 25\dfrac{2}{5}.

(ii) In right-angled ∆ABC

sin x = PerpendicularHypotenuse\dfrac{\text{Perpendicular}}{\text{Hypotenuse}}

= BCAC=1525=35.\dfrac{BC}{AC} = \dfrac{15}{25} = \dfrac{3}{5}.

cos x = BaseHypotenuse\dfrac{\text{Base}}{\text{Hypotenuse}}

= ABAC=2025=45.\dfrac{AB}{AC} = \dfrac{20}{25} = \dfrac{4}{5}.

Substituting the values in 2 sin x - cos x we get :

2 sin x - cos x=2×3545=6545=25.\Rightarrow \text{2 sin x - cos x} = 2 \times \dfrac{3}{5} - \dfrac{4}{5} \\[1em] = \dfrac{6}{5} - \dfrac{4}{5} \\[1em] = \dfrac{2}{5}.

Hence, 2 sin x - cos x = 25\dfrac{2}{5}.

(iii) Substituting values we get :

1 - sin x + cos y=135+45=53+45=65.\Rightarrow \text{1 - sin x + cos y} = 1 - \dfrac{3}{5} + \dfrac{4}{5} \\[1em] = \dfrac{5 - 3 + 4}{5} \\[1em] = \dfrac{6}{5}.

Hence, 1 - sin x + cos y = 65\dfrac{6}{5}.

(iv) By formula,

tan x = sin xcos x=3545=34\dfrac{\text{sin x}}{\text{cos x}} = \dfrac{\dfrac{3}{5}}{\dfrac{4}{5}} = \dfrac{3}{4}.

Substituting values we get :

2 cos x - 3 sin y + 4 tan x=2×453×35+4×34=8595+3=89+155=145.\Rightarrow \text{2 cos x - 3 sin y + 4 tan x} = 2 \times \dfrac{4}{5} - 3 \times \dfrac{3}{5} + 4 \times \dfrac{3}{4}\\[1em] = \dfrac{8}{5} - \dfrac{9}{5} + 3 \\[1em] = -\dfrac{8 - 9 + 15}{5} \\[1em] = \dfrac{14}{5}.

Hence, 2 cos x - 3 sin y + 4 tan x = 145\dfrac{14}{5}.

Answered By

30 Likes


Related Questions